(3ef cJGH GdENdGUs - (3GdEScfOQ Cgejfs
(3ChdgG (B:s
(3ef GdebGdI GdChdi cd UfGYI hePgH hgeg haYd hENJHGQ aEfg jXf Hg Cfg jYXg Edi NjQ eG aGdNjQ gh GdPi fJThbg s
(3BNQgG (B:s
(3hEf cGf ef GdCUfGa agh ef WHjYI GdcGFfGJ GdaGSOGJ hHGdLedI aef YQa GdYOGdI Sgd Ydjg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B15s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdadSaI hGdefWbs